Undergraduate Students’ Self-Regulated Learning in the Use of Mobile Assisted Language Learning (MALL) - Cantika Sari Dewi; Agus Widyantoro; Rezki Suci Qamaria (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah kendari, 2025)
Mobile Assisted Language Learning (MALL) has been increasingly recognized for its potential to enhance English language proficiency, particularly when learners are able to effectively self-regulate their learning. This study aims to examine the level of self-regulated learning (SRL) among undergraduate students in their use of MALL, and to investigate whether differences in SRL exist based on gender and socioeconomic status. Employing a quantitative survey design, this study involved 207 undergraduate students at IAIN Kediri who were using MALL as part of their preparation for the English proficiency test. Data were collected through questionnaires and analyzed using descriptive statistics and the Kruskal-Wallis test, as the data did not meet the assumptions of normality and homogeneity required for parametric analysis. Descriptive results showed students had a relatively high level of SRL, with mean scores ranging from 2.66 (SD = 1.006) to 3.62 (SD = 0.577). The Kruskal-Wallis test revealed significant differences in SRL by gender (p = 0.000) and socioeconomic status (p = 0.007), indicating these demographic factors affect how students self-regulate their learning through MALL. The findings suggest future research to examine other influencing variables and consider longitudinal designs to better understand MALL’s long-term effects on language learning.